Management Concept in Quranic Perspective - Ahmad Asrof Fitri (Jurnal Hikmatuna, 2017)
This research aims to critically describe management concept of Quran that is classified into eight functions: planning, organization, staffing, coordination, leadership, motivation, communication, and supervision. This research was library research, a research using text study or literature that needs philosophical and theoretical analysis. This study used descriptive-analytical approach, by explaining Quranic verses based on several themes as classified, then analyzing them by using thematic interpretation method (tafsîr maudhû’î). The results of this study are: (1) planning has to be based on experience and strategy; (2) organization is done by division of work based on position, departments, work specialization, and chain of command with principle of helping each other; (3) in staffing, recruitment is opened to public, with several criteria: capable and trustable, diligent and knowledgeable, and good verbal communication ability; (4) coordination is implemented gradually and will success if the members consolidate; (5) leadership is expressed in three terms: khalîfah for managerial function; imâm as good example; ulî al-amr as policy maker; (6) criteria of ideal manager are democratic, polite, smart, agile, brave, having integrity, honest, and fair; (7) organization needs special division for religious and spiritual assistance to motivate all members; (8) there are four types of communication which are qaul layyin, qaul maysȗr, qaul balîgh, and qaul ma’rûf, with three phases of method: da’wah bi al-hikmah, mau’izhah hasanah, and mujâdalah bi al-latî hiya ahsan; (10) there are three types of supervision: direct and indirect performance recording, and direct inspection.